Determinants qualitity of financial reports with government internal control system - Purnama Sari, Devi; Nurmala Sari, Eka; Astuty, Widia (Jurnal Mantik, 2024)
The purpose of this study was to determine, test and analyze the effect of applying government accounting standards, utilization of regional financial information systems and human resource competence on the quality of financial reports, with the government's internal control system as a moderating variable This study used a quantitative associative approach with data collection techniques through distributing questionnaires to the Regional Government Organizations of the Medan City Government. The population used in this study were 30 Regional Government Organizations of the Medan City Government. The sample in this study was taken by 3 people from each of the 30 Regional Government Organizations of the Medan City Government consisting of the head/secretary of the OPD, the head of the finance sub-division and the treasurer of Expenditure so that a total of 90 respondents were obtained. Data analysis techniques in this study used the Partial Least Square (PLS) based Structural Equation Modeling (SEM) method. The results showed that the application of government accounting standards had an effect on the quality of financial reports, the use of regional financial information systems had an effect on the quality of financial reports and the competence of human resources had an effect on the quality of financial reports. The government's internal control system can moderate the effect of implementing government accounting standards on the quality of financial reports, the government's internal control system cannot moderate the effect of using regional financial information systems on the quality of financial reports and the government's internal control system can moderate the influence of human resource competence on the quality of financial reports in Medan City Government Regional Apparatus Organization